Assessment of central venous catheterization in a simulated model using a motion-tracking device: an experimental validation study. (December 2016) - Varas, Julián; Achurra, Pablo; León, Felipe; Castillo, Richard; Fuente, Natalia; Aggarwal, Rajesh; Clede, Leticia; Bravo, María; Corvetto, Marcia; Montaña, Rodrigo
Abstract Background Central venous catheterization (CVC) is a basic requirement for many medical specialties. Simulated training in CVC may allow the acquisition of this competency but few reports have established a valid methodology for learning and acquiring procedural skills for CVC. This study aims to validate the use of a tracking motion device, the imperial college surgical assessment device (ICSAD), by comparing it with validated global rating scales (GRS) to measure CVC performance in a simulated torso. Methods Senior year medical students, first and last year residents (PGY1, LYR), and expert anesthesiologists performed a jugular CVC assessment in a simulated model (Laerdal IV Torso). A validated GRS for objective assessment of technical skills and motion analysis by ICSAD was used. Statistical analysis was performed through Mann–Whitney and Kruskal–Wallis tests for construct validity and Spearman correlation coefficients between the ICSAD and GRS scores for concurrent validity between both. Results 32 subjects were recruited (10 medical students, 8 PGY1, 8 LYR and 8 experts). Total path length measured with ICSAD and GRS scores were significantly different between all groups, except for LYR compared to experts (p = 0.664 for GRS and p = 0.72 for ICSAD). Regarding jugular CVC procedural time, LYR and experts were faster than PGY1 and MS (p < 0.05). Spearman correlation coefficient was −0.684 (p < 0.001) between ICSAD and GRS scores. Conclusions ICSAD is a valid tool for assessment of jugular CVC since it differentiates between expert and novice subjects, and correlates with a validated GRS for jugular CVC in a simulated torso.